Dampak Keberadaan PT. Lontar Papyrus Pulp And Paper Industri Terhadap Kondisi Sosial Ekonomi Masyarakat Kelurahan Tebing Tinggi - Hanny Musyayyadah; Sucipto Sucipto; Erwin Saputra Siregar (Universitas 45 Surabaya, 2023)
This research is motivated by the changes that have occurred in society due to the establishment of PT. Lontar Papyrus Pulp and Paper Industry which has positive and negative impacts on society. The purpose of this study was to determine the effect of the existence of a factory on the socio-economic conditions of the people living around the factory. The socio-economic conditions referred to are employment, livelihoods, economic income, social interaction, health and infrastructure development.This study used a qualitative research method with a descriptive approach. The data sources of this research are primary data and secondary data. Data collection techniques through observation, interviews and documentation. The results of this study are: 1) The economic and social conditions of the Tebing Tinggi villagers are that labor absorption has not been maximized, livelihoods that originally came from farmers have been diverted to industrial workers, economic income is uncertain. and depend on the crops growing every month to generate income. Health awareness is very good when the average person has health insurance, social interaction in the community is well established, and infrastructure development is evenly distributed before the existence of industry. 2) The resulting impacts are (a) the positive impact of the existence of factories, namely reducing unemployment, attracting jobs not only from among workers but also partnering with other industries, securing livelihoods for many people opening other non-industrial businesses, growing wealth and ownership health insurance fairness, good relations between native and migrant villagers, (b) Side effects include social jealousy, land change, consumption patterns, pollution and road damage.